High-precision multiwavelength eclipse photometry of the ultra-hot gas giant exoplanet WASP-103 b. Issue 2 (13th November 2017) - Delrez, L; Madhusudhan, N; Lendl, M; Gillon, M; Anderson, D R; Neveu-VanMalle, M; Bouchy, F; Burdanov, A; Collier-Cameron, A; Demory, B-O; Hellier, C; Jehin, E; et al.
Abstract: We present 16 occultation and three transit light curves for the ultra-short period hot Jupiter WASP-103b, in addition to five new radial velocity measurements. We combine these observations with archival data and perform a global analysis of the resulting extensive data set, accounting for the contamination from a nearby star. We detect the thermal emission of the planet in both the z ΄ and K S bands, the measured occultation depths being 699±110 ppm (6.4σ) and 3567_-350^+400 ppm (10.2σ), respectively. We use these two measurements, together with recently published HST/WFC3 data, to derive joint constraints on the properties of WASP-103b's dayside atmosphere. On one hand, we find that the z ΄ band and WFC3 data are best fit by an isothermal atmosphere at 2900 K or an atmosphere with a low H2 O abundance. On the other hand, we find an unexpected excess in the K S band measured flux compared to these models, which requires confirmation with additional observations before any interpretation can be given. From our global data analysis, we also derive a broad-band optical transmission spectrum that shows a minimum around 700 nm and increasing values towards both shorter and longer wavelengths. This is in agreement with a previous study based on a large fraction of the archival transit light curves used in our analysis. The unusual profile of this transmission spectrum is poorly matched by theoretical spectra and is not confirmed by more recent observations at higher spectral resolution. Additional data, in both emission and transmission, are required to better constrain the atmospheric properties of WASP-103b.